Dark scenes from damaged earth : the gothic Anthropocene - Edwards, Justin D., 1970-; Graulund, Rune; Höglund, Johan Anders (University of Minnesota Press, 2022)
"More than just spooky, moonlit castles and morbid graveyards, the Gothic represents a vibrant, emergent perspective on the Anthropocene. In this volume, more than a dozen scholars show that the Gothic offers a unique (and dark) interpretation of events like climate change, diminished ecosystems, and mass extinction"--